Hubungan Persiapan Kelahiran Adik Baru terhadap Kejadian Sibling Rivalry pada Anak Pertama - Roslaini " "; Yufitriana " Amir; Yesi " Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractSibling rivalry is a jealousy and hate that are usually experienced by a child to the presence of the birth of a sibling. The feelings come because of the changes of the condition or the circumstances when the older child had not been prepared before. This research aimed to know and to determine of the relationship of the birth of a new baby preparation on the incidence of the sibling rivalry to the first child with the descriptive research design correlation by using retrospective approach. There were 132 respondents research samples who taken based on the inclussion criteria namely the mothers who have more than one child, the mothers who lived in working area of The Community Health Centre (Puskesmas) Sungai Sembilan, both children who live at home and their pregnancies spacing between the first and the second child is 2 - 4 years by using purposive sampling. The measuring instrument used is the birth questionnaire preparation of a new baby and the incidence of the sibling rivalry to the first child. The analysis used is univariate analysis to know the distribution of the frequncy and bivariate analysis used Chi Square Test to explore the variable relationship between the new baby birth preparation and the incidence of sibling rivalry to the first child. The result of the univariate analysis research showed that most of  the respondents aged 26 - 35 years (75%), moslem (95,5%), javanese (57,6%), elementary graduate (46,2%), servant/ house keepers (87,9), with 2 children (87,9%), the first marriage (97%), the birth of a new baby preparation (52,3%) and occured sibling rivalry (52,3%). The result of the biviariate analysis showed that there is no relationship between a new baby birth preparation to the incidence of the sibling rivalry to the first child. Keywords: Preparation of birth, sibling rivalry